2020
DOI: 10.1021/acscatal.9b05499
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Electrocatalytic Activity of Pd/M (M = Ni, Mn) Nanoparticles for the Oxygen Reduction Reaction in Alkaline Media through Electrochemical Dealloying

Abstract: We have developed a facile and effective electrochemical dealloying strategy to enhance the electrocatalytic activity of Pd/M (M = Ni, Mn) nanoparticles for the oxygen reduction reaction (ORR) in alkaline media. The enhancement arises from the higher atomic concentration of electrochemically active Pd exposed on the surface of the nanoparticles as a result of the electrochemical dealloying process, which was verified by electron energy loss spectroscopy elemental mapping, X-ray photoelectron spectroscopy, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
86
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 43 publications
3
86
1
Order By: Relevance
“…This process is qualitatively similar to electrochemical dealloying previously used to make porous battery materials and catalysts. [28][29][30][31][32][33] We postulate that the increased observed activity for our catalyst compared to Co 3 O 4 may be due in part to an increased surface area after V-dissolution. Unfortunately, we were not able to harvest sufficient amounts of material post-CCE for BET gas adsorption measurements.…”
mentioning
confidence: 75%
“…This process is qualitatively similar to electrochemical dealloying previously used to make porous battery materials and catalysts. [28][29][30][31][32][33] We postulate that the increased observed activity for our catalyst compared to Co 3 O 4 may be due in part to an increased surface area after V-dissolution. Unfortunately, we were not able to harvest sufficient amounts of material post-CCE for BET gas adsorption measurements.…”
mentioning
confidence: 75%
“…[1][2][3][4] Recent investigations have shown that the electrocatalytic efficiency of the Pdbased catalysts can be improved systematically and significantly to match those of Pt by adopting innovative design strategies, tailoring their surfaces by means of facet engineering or alloy formation and tuning of substrate-catalyst interactions. [5][6][7][8][9][10][11] However, two outstanding challenges in AFCs while using Pd nanocrystals (NCs) remain to-date: i) overcoming the sluggish ORR kinetics to further reduce the Pd requirement to match a target set by U.S. Department of Energy, and ii) the absence of sustained highcatalytic activity for prolonged time-periods under the electrochemical operating environments. 6,8,12 Therefore in the existing device prototypes, a larger amount of noble metal is loaded on to the electrode surfaces to attain a sufficient durability.…”
Section: Introductionmentioning
confidence: 99%
“…has emerged as a preferred strategy to modulate the surface electronic structure for improved catalytic activity, and to reduce the noble metal load at the same time. [7][8][9][11][12][13][14][15] The electrons in the 'other' metals hybridize with the d electrons of Pd to lower the 'd-band center' effecting a favorable modulation of the bond-strengths of the ORR intermediates. 16,1718 Besides, the lattice strain invoked by smaller sizes of the alloying atoms also helps in attenuating the intermediate binding energies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, their pseudo‐homogeneous behavior in solution owing to the nano‐sized dimension (<10 nm) combined with the advantages of a heterogeneous catalyst by supporting on a solid make them perfect candidates for potential industrial applications. Within this context, a large variety of highly productive catalysts based on nanoparticles of Co, [1,2] Mn, [3,4] Rh, [5,6] Ir, [7,8] Pd, [9,10] and Pt [11,12] have been developed for catalytic organic transformation reactions. Among these nanoparticles, Pd metal nanoparticles (PdNPs) have proven to be the most powerful catalyst for many organic syntheses of industrial importance, such as the synthesis of pharmaceuticals, medicines, pesticides, degradation of organic pollutants, C−C bond formation and the hydrogenation reaction [13] .…”
Section: Introductionmentioning
confidence: 99%